Echocardiography in the Assessment of Heart Failure Patients - Frank L. Dini; Matteo Cameli; Andrea Stefanini; Hatem Soliman Aboumarie; Matteo Lisi; Per Lindqvist; Michael Y. Henein (Diagnostics)
Doppler echocardiography is the corner-stone of non-invasive investigation of patients with a clinical diagnosis of heart failure. It provides an accurate and quantitative assessment of cardiac structure and function. Furthermore, spectral Doppler measurement is an invaluable technique for estimating intracardiac pressures with their crucial value in the optimum management of heart failure patients, irrespective of ejection fraction. Speckle tracking echocardiography stretches the unique application of echocardiography to analyze the myocardial deformation function which has proved very accurate in detecting ischemia, dyssynchrony, subclinical dysfunction and also in estimating pulmonary capillary wedge pressures. The role of longitudinal myocardial left atrial deformation dynamics has recently emerged as a valuable tool for assessing left ventricular diastolic dysfunction in patients with cardiac diseases regardless of their ejection fraction. Finally, the extent of myocardial deformation has been shown to correlate with the severity of myocardial fibrosis, a common finding in patients with heart failure.